From the Approach to the Concept: One Health in Latin America-Experiences and Perspectives in Brazil, Chile, and Colombia - Pettan-Brewer, Christina; Martins, Andreza Francisco; Abreu, Daniel Paiva Barros de; Brandão, Ana Pérola Drulla; Barbosa, David Soeiro; Figueroa, Daniela P.; Cediel, Natalia; Kahn, Laura H.; Brandespim, Daniel Friguglietti; Velásquez, Juan Carlos Carrascal; Carvalho, Adolorata Aparecida Bianco; Takayanagui, Angela Maria Magosso; et al. (Frontiers in Public Health, 2021)
Professionals throughout the world have been working to assess the interdisciplinary interaction and interdependence between health and wellbeing in a constantly changing environment. The One Health concept was developed to encourage sustainable collaborative partnerships and to promote optimal health for people, animals, plants, the environment, and the whole planet. The dissemination of scientific discoveries and policies by working directly with diverse communities has been one of the main goals for Global One Health. The One Health concept has also been referred or related to as “One Medicine; One Medicine-One Health; One World-One Health; EcoHealth and Planetary Health” depending on each fundamental views and approaches. In Latin America, despite the concept is still being discussed among health professionals and educators, several One Health initiatives have been daily used for more than decades. One Health actions have been applied especially in rural and underserved urban areas where low socioeconomic status, lack of health professionals, and scarcity of medical resources may really require professionals working together as One. Local communities from diverse social and economic status, including indigenous populations, have been working with institutions and social organizations for many years, accomplishing results through grassroots movements. These “bottom-up” socio-community approaches, have been also tools for prevention and control diseases. Such practice has preceded the One Health concepts in Latin American countries. We strongly believe that collaborative, multidisciplinary, political, and economic initiatives with prosocial focus may become investments towards obtaining significant results in the face of global economic and health challenges: working for a healthier world with inclusivity, equity, and equality. Here, we briefly present how the One Health approach has been initiated and developed in Latin America, highlighting the events and actions taken in Brazil, Chile, and Colombia.